2016
DOI: 10.7727/wimj.2016.095
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Dengue Outbreaks in Resource Limited Facilities

Abstract: Objective: Dengue is a re-emerging public health problem threatening the tropical developing world, mandating rapid diagnosis and supportive management in the absence of licensed vaccines or anti-dengue therapy. Regions endemic to dengue and related viruses are overwhelmed by the sudden surge of cases during outbreaks. It is difficult to justify confirmatory diagnosis of every case using The World Health Organization (WHO) criteria or differentiate it from other concurrent viral illnesses. The study evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Open surgical modalities are more invasive and may be inaccessible or unaffordable by patients in developing countries. 13 Various agents used as fibrinolytics like streptokinase, urokinase and tissue Plasminogen Activator can be used intra-pleurally. 14,15 Although there are existing controversies in the choice of fibrinolytic drug, 33 000 kDa low-molecular-weight urokinase is preferred over streptokinase due to rapid plasma half-life and ability to directly activate plasminogen to form plasmin.…”
mentioning
confidence: 99%
“…Open surgical modalities are more invasive and may be inaccessible or unaffordable by patients in developing countries. 13 Various agents used as fibrinolytics like streptokinase, urokinase and tissue Plasminogen Activator can be used intra-pleurally. 14,15 Although there are existing controversies in the choice of fibrinolytic drug, 33 000 kDa low-molecular-weight urokinase is preferred over streptokinase due to rapid plasma half-life and ability to directly activate plasminogen to form plasmin.…”
mentioning
confidence: 99%
“…[7][8][9] The Hajj is regarded as the best mass gathering preparedness effort worldwide; nevertheless, the history of the Hajj is replete with heat illnesses. Major contributors to overall heat stress are mean temperatures reaching 45°C, humidity approaching 80%, and stagnant atmospheric conditions potentiated by heat dissipation from asphalt and concrete surfaces, vehicle exhaust, Hajj crowds, and human activities.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a tendency to severe traveler's diarrhea or patients on antacids need to be vigilant in food and water choices while traveling to tropical countries. [24][25][26][27] The current study revealed a young patient profile suffering from Salmonella bacteremia. The high degree of resistance to fluoroquinolones is alarming among all serotypes, viz.…”
Section: Discussionmentioning
confidence: 99%